The audit and the levels of tax evasión - Rengifo Lozano, Raúl (2018)
In our country, SUNAT has been making great efforts in order to guide all those taxpayers who do not comply with their tax obligations to the State, as well as those who must pay taxes and have never done so. In this context, it is very difficult to detect those people who have never been taxed and who are within the informal economy, likewise, it is even more complicated to determine those people who are taxed, but they do it in an improper way. The present study is descriptive, correlational and of an applicative nature; getting to demonstrate that the audit has an impact on the tax evasion controls.